The United States and the Development of the Puerto Rican Status Question, 1936 -1968 - Bhana, Surendra (University Press of Kansas, 1975)
This study traces the evolution of political status in Puerto Rico from 1936 to 1968, with special emphasis on the events that led to the creation of the Commonwealth in 1952. No other work published in English has dealt with the Puerto Rican status question in such detail.The central problem in the status debate has been: how to strike a happy balance between Puerto Rico's economic needs, which could be filled through uninterrupted association with the United States, and the cultural divergence between the mainland and the island. Bringing together new and significant information drawn from government records and personal papers of U.S. officials, this book will be of interest to all serious students of Puerto Rican affairs, as well as to U.S. and Puerto Rican government and political leaders.